Do 6-Month Motor Skills Have Cascading Effects on 12-Month Motor and Cognitive Development in Extremely Preterm and Full-Term Infants? - Zuccarini, Mariagrazia; Guarini, Annalisa; Savini, Silvia; Faldella, Giacomo; Sansavini, Alessandra (Frontiers in Psychology, 2020)
In this study, we analyzed whether 6-month gross and fine motor skills were related to 12-month gross and fine motor skills and cognitive development, controlling for 6-month cognitive skills and neonatal status (extremely low gestational age ELGA ≤ 28 weeks vs. full-term FT ≥ 37 weeks). We also investigated, at 6 months, predictive indexes for motor and cognitive delay at 12-months. We assessed 40 infants (20 ELGA and 20 FT) at 6 and 12 months (corrected age for the ELGA infants). Six-month gross motor skills were related to 12-month gross motor, fine motor, and cognitive skills and predicted 12-month gross motor delay. Six-month cognitive skills explained an additional amount of variance of 12-month gross motor skills, whereas neonatal status explained an additional amount of variance of 12-month cognitive skills. Considering the intradomain and cross-domain cascading effects of early gross motor skills on later motor and cognitive development, these skills should be repeatedly assessed in ELGA infants in the first year of life for early identification of infants with delayed gross motor skills and implementation of customized interventions.